In-vivo analysis of ankle joint movement for patient-specific kinematic characterization. (September 2017) - Ferraresi, Carlo; De Benedictis, Carlo; Franco, Walter; Maffiodo, Daniela; Leardini, Alberto
In this article, a method for the experimental in-vivo characterization of the ankle kinematics is proposed. The method is meant to improve personalization of various ankle joint treatments, such as surgical decision-making or design and application of an orthosis, possibly to increase their effectiveness. This characterization in fact would make the treatments more compatible with the specific patient's joint physiological conditions. This article describes the experimental procedure and the analytical method adopted, based on the instantaneous and mean helical axis theories. The results obtained in this experimental analysis reveal that more accurate techniques are necessary for a robust in-vivo assessment of the tibio-talar axis of rotation.